PENGARUH SELF EFFICACY, TEKANAN KETAATAN, LOCUS OF CONTROL, DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT - Satiman Satiman (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2018)
The objective of this research was to examine the influence of self efficacy, obedience pressure, locus of control and task  complexity on audit judgment.  The   respondents are auditor who working in public accountant firm in South Jakarta. 133 questionnaires are distributed, 102 questionnaires are returned and analyzed in this research. Hypothesis testing is done by multiple  regression  analysis method and assisted tool SPSS 22 statistical test.The research showed that influence of self efficacy, obedience pressure, locus of control and task complexity has signficant to audit judgment.